Genome-Wide Association Study Uncovers Novel Genomic Regions Associated With Coleoptile Length in Hard Winter Wheat - Sidhu, Jagdeep Singh; Singh, Dilkaran; Gill, Harsimardeep Singh; Brar, Navreet Kaur; Qiu, Yeyan; Halder, Jyotirmoy; Al Tameemi, Rami; Turnipseed, Brent; Sehgal, Sunish Kumar (Frontiers in genetics, 2020)
Successful seedling establishment depends on the optimum depth of seed placement especially in drought-prone conditions, providing an opportunity to exploit subsoil water and increase winter survival in winter wheat. Coleoptile length is a key determinant for the appropriate depth at which seed can be sown. Thus, understanding the genetic basis of coleoptile length is necessary and important for wheat breeding. We conducted a genome-wide association study (GWAS) using a diverse panel of 298 winter wheat genotypes to dissect the genetic architecture of coleoptile length. We identified nine genomic regions associated with the coleoptile length on seven different chromosomes. Of the nine genomic regions, five have been previously reported in various studies, including one mapped to previously known region. Three novel quantitative trait loci (QTLs), , , and were identified in our study. has a large substitution effect which is comparable to 's effect and could be used to compensate for the negative effect of on coleoptile length. In total, the nine QTLs explained 59% of the total phenotypic variation. Cultivars 'Agate' and 'MT06103' have the longest coleoptile length and interestingly, have favorable alleles at nine and eight coleoptile loci, respectively. These lines could be a valuable germplasm for longer coleoptile breeding. Gene annotations in the candidate regions revealed several putative proteins of specific interest including cytochrome P450-like, expansins, and phytochrome A. The QTLs for coleoptile length linked to single-nucleotide polymorphism (SNP) markers reported in this study could be employed in marker-assisted breeding for longer coleoptile in wheat. Thus, our study provides valuable insights into the genetic and molecular regulation of the coleoptile length in winter wheat.